2003
DOI: 10.1124/jpet.102.041871
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Rho-Kinase Reduces Renal Na-H Exchanger Activity and Causes Natriuresis in Rat

Abstract: Rho-kinase regulates the actin cytoskeleton and therefore modulates transport. The role of Rho-kinase in Na-H exchanger (NHE) activity of rat proximal convoluted tubules (PCTs) was investigated using (R)-(ϩ)-trans-N-(4-pyridyl)-4-(1-aminoethyl)-cyclohexanecarboxamide (Y-27632), a specific inhibitor of Rho-kinase. In spontaneously hypertensive rats (SHR) and Wistar Kyoto (WKY) rats, apical and basolateral NHE activities were determined by measuring cell pH recovery following luminal NH 4 ϩ prepulse and basolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…It should be emphasized that ANG II has direct stimulatory effects on Na ϩ reabsorption, an action that could be independent of Rho kinase. Nishiki et al (24) reported recently that Y-27632 caused a natriuresis in normal and hypertensive rats by reducing the activity of the Na ϩ /H ϩ exchanger in the proximal nephron. They used a continuous infusion of a nonhypotensive dose of the drug, and because they carefully monitored MAP, they were able to discard experiments in which MAP decreased by Ͼ5% of the basal level.…”
Section: Discussionmentioning
confidence: 98%
“…It should be emphasized that ANG II has direct stimulatory effects on Na ϩ reabsorption, an action that could be independent of Rho kinase. Nishiki et al (24) reported recently that Y-27632 caused a natriuresis in normal and hypertensive rats by reducing the activity of the Na ϩ /H ϩ exchanger in the proximal nephron. They used a continuous infusion of a nonhypotensive dose of the drug, and because they carefully monitored MAP, they were able to discard experiments in which MAP decreased by Ͼ5% of the basal level.…”
Section: Discussionmentioning
confidence: 98%
“…70,71 In vivo, high blood pressure in SHR is associated with a decreased renal Na C excretion and a significant increase in NHE3 activity. 72 These parameters are reversed by treatment with the Rock inhibitor Y27632. 72 …”
Section: Regulation Of Epithelial Namentioning
confidence: 99%
“…In fact, RhoA and Rho-kinase, by controlling the phosphorylation of MLC and, ultimately, the organization of the actin cytoskeleton, are important for NHE3 association with ezrin and actin, and this interaction is required for maintenance of the exchanger at the apical surface (159,474). In SHR, hypertension is associated with a marked increase in NHE3 activity and a decreased Na ϩ excretion (338). Inhibition of Rho-kinase by Y27632 reduces apical NHE3 activity and enhances Na ϩ excretion and total urine volume (338).…”
Section: Role Of Rho Proteins On Sodium-hydrogen Exchangermentioning
confidence: 99%
“…In SHR, hypertension is associated with a marked increase in NHE3 activity and a decreased Na ϩ excretion (338). Inhibition of Rho-kinase by Y27632 reduces apical NHE3 activity and enhances Na ϩ excretion and total urine volume (338). Because, in general, a natriuresis in patients with hypertension reduces blood pressure, it has been suggested that the natriuresis induced by Y27632 may contribute to its blood pressure lowering effect (474).…”
Section: Role Of Rho Proteins On Sodium-hydrogen Exchangermentioning
confidence: 99%